2005
DOI: 10.1002/cta.302
|View full text |Cite
|
Sign up to set email alerts
|

Pixel‐level snakes on the CNNUM: algorithm design, on‐chip implementation and applications

Abstract: SUMMARYIn this paper, a new algorithm for the cellular active contour technique called pixel-level snakes is proposed. The motivation is twofold: on the one hand, a higher e ciency and exibility in the contour evolution towards the boundaries of interest are pursued. On the other hand, a higher performance and suitability for its hardware implementation onto a cellular neural network (CNN) chip-set architecture are also required. Based on the analysis of previous schemes the contour evolution is improved and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…PLS [2][3][4][5] is an evolved version of the original snake algorithm. In PLS algorithm, two forces from the internal energy and the external potential are calculated, and the motion of the curve is determined at the pixel level by the dominant force between these two forces.…”
Section: Contour-expansion Version Of Ca-based Plsmentioning
confidence: 99%
See 2 more Smart Citations
“…PLS [2][3][4][5] is an evolved version of the original snake algorithm. In PLS algorithm, two forces from the internal energy and the external potential are calculated, and the motion of the curve is determined at the pixel level by the dominant force between these two forces.…”
Section: Contour-expansion Version Of Ca-based Plsmentioning
confidence: 99%
“…The conventional PLS algorithm [2][3][4][5] is based on a CNN [8]. A CNN is a kind of neural network whose connectivity is only restricted to adjoining cells.…”
Section: Contour-expansion Version Of Ca-based Plsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows a block diagram with the main modules to be implemented in a PLS algorithm. A comprehensive review of PLS can be found in [6].…”
Section: Pixel Level Snakesmentioning
confidence: 99%
“…PLS have been implemented on hardware architectures with pixel-parallel processing capabilities, such as ACE4K [6,7] (based on cellular neural network paradigm) and SCAMP-3 [8,9] (based on SIMD processor array). As a consequence a high speed of processing is achieved.…”
Section: Pixel Level Snakesmentioning
confidence: 99%